Hypoplasia of the ipsilateral internal jugular vein is associated with worse outcome in acute anterior circulataion stroke - Vukicevic, Marjana; Georgievski Brkić, Biljana; Jaramaz Dučić, Tatjana; Vojvodić, Ljubica; Mileusnić, Valentina; Raičević, Ranko (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Disruption of cerebral venous blood drainage leads to cerebral venous congestion, an increase in intracranial pressure and decrease of the cerebral perfusion pressure. The exact role of the cerebral venous circulation in acute stroke is not yet known. The main blood drainage from the brain and the superficial parts of the face and neck is drained by a paired internal jugular vein (IJV). Congenital anomalies of IJV may disrupt the blood collection from the brain, which leads to congestion of the cerebral venous circulation. The aim of our study was to determine the association between the hypoplastic ipsilateral IJV and clinical outcome of patients with acute ischemic anterior circulation stroke. Methods. This prospective case series study involved the patients with the anterior circulation stroke and ultrasonographic criteria for unilateral hypoplasia of the ipsilateral IJV. Data from the 74 consecutive patients with acute anterior circulation stroke admitted to the Special Hospital for Cerebrovascular Diseases “Sveti Sava”, Belgrade, from September 2015 to January 2016 were included. Ultrasonography of IJV diameter and the collection of the hemodynamic data were performed in all patients. Neurological deficits on admission were evaluated using the National Institutes of Health Stroke Scale (NIHSS) score. The clinical outcome was assessed using the modified Rankin Scale (mRS) score (from 0 to 6) at 30 days or at discharge, whichever occurred sooner. Good and poor outcomes were defined as an mRS score of 0–2 and 3–6, respectively. Results. Ipsilateral hypoplastic IJV was diagnosed in 13 (17.6%) patients with anterior circulation stroke. In this group, 9 stroke patients (69.2%) had mRS ≥ 3. Of the remaining 4 patients with mRS ≤ 2, three had bilateral hypoplasia of IJV and one patient had smaller diameter of the IJV, but did not fulfill the ultrasonographic criteria for hypoplastic venous anomaly. Conclusions. In our case, a series of the patients with anterior circulation stroke with ultrasonographic criteria for unilateral hypoplasia of the ipsilateral IJV (on stroke side) have worse clinical outcome compared with the patients with bilateral hypoplasia.
Keywords: brain infarction; jugular veins; echocardiography, doppler; treatment outcome